Effect of Leg Length Discrepancy to the Hip Function on Post Hemiarthroplasty Patients in Jember - Yosalfa Adhista Kurniawan; Muhammad Hasan; Rena Normasari (Journal of Agromedicine and Medical Sciences, 2017)
Hip fractures in elderly patient are often treated with hemiarthroplasty. Hemiarthroplasty can cause various complications, one of which is leg legth descrepancy (LLD). The function of the hip joint is reduced due to these complications. Previous studies have shown contradictive results regarding the relationship of LLD to the function of the hip joint in post-arthroplasty patient's. This type of research is observational with retrospective study. The population in this study came from 2 hospitals in Jember was 53 patients and the sample was 30 people. LLD is measured by true leg length and apparent leg length, whereas hip joint function is measured by Oxford Hip Score (OHS). The data were tested by using Spearman correlation test. In conclusion, there was a moderate relationship between LLD true leg length to the function of the hip joint. This study does not support the implications of the LLD to the hip function because of weak relationship between LLD true leg to the hip function and moderate relasionship between LLD apparent leg length to the hip function.